Pola Pengembangan Pembelajaran Digital Berbasis Interactive Whiteboard untuk Sekolah Swasembada Pangan dengan Pendekatan Astacita OOPP di KB/TK Lab UM - Hendra Susanto; Agung Witjoro; Deny Setiawan; Jasmine Nurul Izza; Celiacika Gustisiwi Puteri (IAI Nasional Laa Roiba Bogor, 2026)
This study aims to describe the development pattern of digital learning based on Interactive Whiteboard (IWB) in supporting the implementation of food self-sufficiency schools at the early childhood education level. The approach used in this development refers to the vision of national development in Asta Cita as well as the Oriented-Outcome Project Planning (OOPP) framework which emphasizes the achievement of project-based learning outcomes and impacts. The research was conducted in KB/TK Laboratory of the State University of Malang using a qualitative descriptive method. Data collection was carried out through participatory observation, in-depth interviews with teachers and students, and documentation of the learning process. The results showed that the use of IWB can increase children's involvement in thematic learning based on local food, strengthen the visualization of the plant-harvest process interactively, and encourage children's motor and collaborative skills. The development pattern of digital learning through IWB which is integrated with OOPP and Asta Cita forms a contextual learning ecosystem, with a food security perspective, and based on the nation's character.